Can Polish Voivodeships Cities Use Mobile Apps? - Leszek GRACZ (Communications of International Proceedings, 2021)
Objective – The objective of the paper is to evaluate the usage of mobile apps by Polish major cities. The actual usage and opinions about the apps are taken into consideration to meet the objective. Methodology – The cities that are subject of research are the cities that are the place of residence of the voivodeship governor (Polish: wojewoda) and/or a place of voivodeship parliament. The 18 cities were studied. These are also the main and the biggest cities in Poland. Basing on the list of mobile apps created by / ordered by local governments the following data were obtained for each selected app: the number of comments, the average evaluation (with the scale 1-very bad; 5 - very good), category (using Google Play store categories, namely: business, travel & local, transport, social, sport, skill app, weather, maps & navigation, books & reference, tools) and the number of downloads. The data were then analyzed using pivot table in Microsoft Excel. Findings – Polish major cities try to utilize the possibilities provided by mobile apps. The new ones keep appearing, while most of the old ones are abandoned (they are no longer available in Google Play store and no longer supported or updated). However, there is a disturbing trend. From relatively high evaluation of cities' apps in 2015 (average rating 4,3), the rating lowered significantly in 2021 (to average 3,2). There is a clear gap between users' expectations and delivered value. Polish major cities should carefully examine this situation. A good starting point is understanding the key success factors of the few researched apps with high ratings and downloads. Originality/value – The study contributes to the literature on mobile apps used by e-governments.
Keywords: mobile apps; e-government; Polish cities.